Diseño arquitectónico de un centro geriátrico integral - Murillo, Rubén (2019)
The purpose of the present work is to carry out an integral architectural design for the development of a geriatric center, to promote the adequate assistance and necessary treatments for the care of the elderly without neglecting their role in society as citizens and their right to urban spaces. The sample is based on two important centers of the city: Hogar Corazón de Jesús and Hogar San José. User surveys were carried out, the selection of the sample chosen was arbitrary and the questions asked were subjective, but with simple answers about the services from which they benefit. The author conduct interviews with users and administrative staff from each of the centers, with questions more oriented to activities they carry out in the spaces. The users of the geriatric centers prefer centers to be in the city to be close with their loved ones, rejecting the idea of geriatrics in the perimeters or outside. Also, all the respondents mentioned their displeasure to the closures of the geriatric, desiring the free displacement to the city. In the two geriatric centers, users prefer the hours in the gardens enjoying the interaction with children and young people; these spaces become a priority. The importance of the research is to analyze the functional spaces of the two geriatrics in the city of Guayaquil, to know areas that work accordingly and identify necessary spaces of the users for future architectural projects of Geriatric Centers.